Hybridization of Islamic Education and Neurosciences: A Study of Suyadi's Thought - Tahmid Miftachurrozaq; Suyadi Suyadi (Universitas Negeri Jakarta, 2023)
This study analyzes how Islamic education disciplines can be hybridized with neuroscience disciplines. This study employs a qualitative research methodology based on literature review. Data were gathered from a variety of books, periodicals, and other sources, and were then subjected to concept analysis. The results show that Suyadi thoughts on Islamic education and neuroscience can be hybridized. The hybridization then resulted in various new branches of science called Neurosains Pendidikan Islam (NPI). It is can answer the challenges and needs of exploring the human dimension in more detail, from molecular cellular to behavioral regulation and social science. In its implementation, educators and neurologists must make new findings to optimize the brain's working system by stimulating and exploring neuroanatomy and neurophysiology. Hybridization in the independent curriculum can be done by integrating and optimizing the brain's work Hybridization in the independent curriculum can be done by integrating and optimizing the brain's work. There are three dimensions of the brain, namely normal brain, healthy brain, intelligent brain, and character brain. Islamic education neuroscience examines the optimization of the brain's potential for students' intelligence.